Implementing An Innovative Design Charrette: Creating Healing Environments for Clinicians and Patients' Well-being - Susan O'Hara; Stephen Langston; Vincent Della Donna; Robin Toft Klar (The Ohio State University Libraries, 2024)
Clinicians, staff, patients, and visitors use the healthcare environment, and a deeper understanding of spatial elements that promote their well-being is necessary. However, clinical and academic nursing does not naturally fit within the field of architectural design and planning. A design charrette, an interactive and innovative approach for faculty, staff, and clinicians, offers participants a chance to be creative in merging evidence-based practice with evidence-based design principles to aid in well-being. This educational brief outlines the process and outcomes of spaces that promote well-being and restoration. The design example presented is a restorative space in a clinical unit. We describe the methods of this teaching experience and highlight the application of a design charrette for a clinical unit.